Water quality assessment for Ulansuhai Lake using fuzzy clustering and pattern recognition - Ren, Chuntao; Li, Changyou; Jia, Keli; Zhang, Sheng; Li, Weiping; Cao, Youling (Chinese journal of oceanology and limnology, 2008)
Water quality assessment of lakes is important to determine functional zones of water use. Considering the fuzziness during the partitioning process for lake water quality in an arid area, a multiplex model of fuzzy clustering with pattern recognition was developed by integrating transitive closure method, ISODATA algorithm in fuzzy clustering and fuzzy pattern recognition. The model was applied to partition the Ulansuhai Lake, a typical shallow lake in arid climate zone in the west part of Inner Mongolia, China and grade the condition of water quality divisions. The results showed that the partition well matched the real conditions of the lake, and the method has been proved accurate in the application.